2022
DOI: 10.3389/fimmu.2022.987666
|View full text |Cite
|
Sign up to set email alerts
|

A synonymous mutation in PI4KA impacts the transcription and translation process of gene expression

Abstract: Phosphatidylinositol-4-kinase alpha (PI4KIIIα), encoded by the PI4KA gene, can synthesize phosphatidylinositol-4-phosphate (PI-4-P), which serves as a specific membrane marker and is instrumental in signal transduction. PI4KA mutations can cause autosomal recessive diseases involving neurological, intestinal, and immunological conditions (OMIM:619621, 616531, 619708). We detected sepsis, severe diarrhea, and decreased immunoglobulin levels in one neonate. Two novel compound heterozygous mutations, c.5846T&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…The cDNA level with the c.1914G>T mutation results in only up to about 1/3 of the normal cDNA strand. This is similar to our previous synonymous mutation research [11], about which the minigene assay confirmed the nonsense-mediated mRNA decay (NMD), mediated downregulation, which contributes to about one-third of disease-causing mRNAs [12,13]. However, no possible abnormal splice patterns were predicted through splicing prediction software.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The cDNA level with the c.1914G>T mutation results in only up to about 1/3 of the normal cDNA strand. This is similar to our previous synonymous mutation research [11], about which the minigene assay confirmed the nonsense-mediated mRNA decay (NMD), mediated downregulation, which contributes to about one-third of disease-causing mRNAs [12,13]. However, no possible abnormal splice patterns were predicted through splicing prediction software.…”
supporting
confidence: 87%
“…Synonymous mutations are frequently detected from gene sequencing and considered to be nonpathogenic as they do not alter the amino acid of the encoded protein. However, synonymous mutations could also lead to abnormal splicing by creating or altering noncanonical splicing sites, and there are quite a few reports about synonymous variations contributing to abnormal splicing [11]. In our study, the proband has the synonymous variant c.1914G>T (p. L638=) in the JAK3 gene which is inherited from her mother, with location at the 5′ end of exon 14, in which the nucleoside site is against the splicing donor site of the 5′ end of the intron which starts with the G. We speculated that the variant could disturb the donor splice site function.…”
mentioning
confidence: 99%